A clinical field trial on wound healing after disbudding of dairy calves with or without antimicrobial spray - Bijkerk, H. J. C.; Nielen, M.; van Geijlswijk, I. M.; Vernooij, J. C. M.; Jorritsma, R. (Frontiers in Veterinary Science, 2025)
Calves are routinely disbudded with hot iron disbudders in Netherlands. Disbudding wounds are frequently treated with antimicrobial wound spray with the aim of preventing infection and improving wound healing. Given the policy for the prudent use of antimicrobials, we decided to evaluate the effect of antimicrobial wound spray vs. non-antimicrobial wound spray after disbudding in a commercial setting. In this field trial, we treated 255 calves after disbudding with chlortetracycline (CTC) spray and Keno™Fix (KF) on alternating the left and right horn buds. At 1 week and 4 weeks after disbudding, we measured the healing rate (HR) in mm/week and the lesion score (LS) of the wounds. The field conditions on farms were also monitored and investigated for an effect on HR and LS. The HR of KF wounds was numerically lower than CTC wounds but did not pass the non-inferiority threshold of 0.5 mm/week. Lesion scores were worse for KF-treated wounds than for CTC-treated wounds. For both CTC and KF wounds, we found that a worse lesion score was associated with a lower HR. We found that lesion scores were worse for KF-treated wounds and calculated that five calves need to be treated with CTC to prevent one calf from developing an inferior wound score. Since the HR of KF was lower, though not inferior to CTC-treated wounds, we conclude that in certain circumstances, the use of an antibiotic spray after cautery disbudding of calves may not be necessary.